(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of extraocular muscle fenestration surgery in the treatment of horizontal sensory strabismus. Subjects and Methods: A prospective descriptive study was conducted on 37 patients diagnosed with horizontal sensory strabismus who underwent extraocular muscle fenestration in the Pediatric Ophthalmology Department at Vietnam National Eye Hospital from December 2024 to July 2025. Both male and female patients aged ≥16 years were included. Results: The study included 37 patients (mean age 27.2 ± 10.8 years), with the majority aged 16–40 years. The mean preoperative deviation angle was 33.5 ± 12.9 PD in sensory exotropia and 37.7 ± 11.8 PD in sensory esotropia. The surgical success rate (<10 PD) was 83.8% for sensory exotropia and 84.6% for sensory esotropia. Conclusion: Extraocular muscle fenestration achieved high success in ocular alignment, with 83.8% in sensory exotropia and 84.6% in sensory esotropia. The mean deviation angle significantly decreased from 37.7 PD to 2.9 PD (exotropia) and from 33.5 PD to 6.7 PD (esotropia), with stable postoperative outcomes.